Social Change: Bullying on Basic School Children - Elke Mai Syarah (International Journal of Educational Dynamics, 2019)
ABSTRACT Social change is one of the things that is very susceptible to occur in elementery school children. This change occurs due to the child’s lack of existing social change. Indeed , this social change that is very vulnerable to occur in children is bullying. Bullying is often found to occur among elementary school children. This certainly must be a concern in the environment of elementary school children can have consequences for children who are bullied. Their children’s confidence decreases so that in their environtment he does not feel comfort in him. This article aims to provide solutions related to how to deal with bullying that occurs at school. Keywords : Bullying, children, solution